2014
DOI: 10.1111/hex.12216
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' perceptions of shared decision‐making behaviours: a qualitative study demonstrating the continued chasm between aspirations and clinical practice

Abstract: Background Shared Decision Making (SDM) is a process of engaging patients in health decisions that involve multiple medically appropriate treatment options. Despite growing public and policy support for patient engagement in health decisions, SDM is not widely practiced in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 48 publications
(82 reference statements)
4
92
0
Order By: Relevance
“…We also incorporated findings from qualitative studies of non-EPs, due to the paucity of related studies with EPs. [25][26][27][28] Table 1 demonstrates how the theoretical framework guided the development of the interview guide. The interview guide was piloted and was then iteratively revised during the interview process (Data Supplement S1, available as supporting information in the online version of this paper).…”
Section: Methodsmentioning
confidence: 99%
“…We also incorporated findings from qualitative studies of non-EPs, due to the paucity of related studies with EPs. [25][26][27][28] Table 1 demonstrates how the theoretical framework guided the development of the interview guide. The interview guide was piloted and was then iteratively revised during the interview process (Data Supplement S1, available as supporting information in the online version of this paper).…”
Section: Methodsmentioning
confidence: 99%
“…as the authors state, where guidelines exist recommending one treatment option, physicians may feel pressured to follow such recommendations, and thus may be less likely to seek involvement from their patient [32]. One qualitative study of 20 physicians found that support for SDM was most common among those who had received training in SDM related communication skills [33]. Conversely, those who worked under physicians who did not Table 3 Factors associated with support or lack of support for patient involvement in decision making.…”
Section: Physician-related Factors That Impact Support For Sdmmentioning
confidence: 99%
“…10,33,34 The failure to improve decisional quality and SDM in this trial supports the hypothesis that effective patient engagement involves specific clinician behaviors that are learned or prompted. 35,36 This raises the question of whether an intervention must include more deliberate methods to alter clinicians' current healthcare delivery patterns to lead to elicitation and integration of patient values and preferences. Many clinicians feel they already perform SDM regularly; yet, data suggest that attitudes are often not aligned, 35,36 and there is little evidence of proficiency in SDM skills.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 This raises the question of whether an intervention must include more deliberate methods to alter clinicians' current healthcare delivery patterns to lead to elicitation and integration of patient values and preferences. Many clinicians feel they already perform SDM regularly; yet, data suggest that attitudes are often not aligned, 35,36 and there is little evidence of proficiency in SDM skills. 37 Importantly, the high scores on 2 items from the OPTION scale that focused on patient education suggested that the decision aid was often used as an educational pamphlet rather than a tool to facilitate a shared conversation.…”
Section: Discussionmentioning
confidence: 99%